IMPLEMENTASI MANAJEMEN PENDIDIKAN BERBASIS NILAI-NILAI ISLAM DI SDIT : KAJIAN LIBRARY RESEARCH - Baimunah, Siti; Bahrani; Sudadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Integrated Islamic Elementary Schools (SDIT) carry a dual strategic mission: delivering high-quality education while simultaneously cultivating students' character grounded in Islamic values. This study aims to analyze and construct a conceptual framework for the implementation of Islamic values-based educational management in SDIT through a systematic library research approach. A descriptive qualitative method was employed, utilizing content analysis of ten selected peer-reviewed journal articles published between 2021 and 2025. The findings reveal that Islamic values-based educational management in SDIT encompasses five interrelated dimensions: (1) curriculum planning grounded in the principles of syura and tawhid; (2) instructional implementation through values integration and Islamic habituation programs; (3) application of Total Quality Management synergized with the values of amanah and ihsan; (4) spiritual-professional leadership that regards institutional roles as a divine trust (amanah); and (5) student character development through structured worship routines and teacher exemplarity. These findings affirm that Islamic values and modern management principles are not contradictory entities but can be synergistically integrated to produce a holistic, adaptive, and high-quality educational system. This study contributes to the theoretical development of Islamic educational management frameworks, offering practical guidance for practitioners and policymakers within SDIT and comparable Islamic educational institutions.